Leading to Student Teachers’ Success or Low Academic Performance - Karvinen, Ikali; Gosh, Saraswati; Russom, Yohannes; Shumendi, Awet; Mulugeta, Dejen (Open Science Journal, 2018)
This study aimed to investigate factors that are leading to student teachers’ success, or on the other hand, to low academic performance. It focused on four major thematic areas, including 1) Study planning and time management, 2) Relationship with others, 3) Resources, and 4) Motivation and status of the teaching profession. This study took place at the Eritrea Institute of Technology, College of Education, in Eritrea. A participatory qualitative research design with thematic focus group discussions was used. Three focus group discussions with 24 students were conducted. The data was discussed in the research meetings, arranged, and each researcher was given one thematic area for further analysis. The analysis was conducted as a deductive content analysis where the four themes were leading the analysis process. The study shows that study planning and time management is one of the key elements in successful studies. Additionally, access to relevant study resources facilitates learning. Relationship with the other students, with the teachers and family is either supporting or negatively affecting to the academic performance. This study recommends that teacher education institutions should study more the reasons for their students’ both low and high academic performance. This needs multi-stakeholder approach, meaning engagement and co-operation of parents, teachers, students and governmental and non-governmental administrations.